A legacy of fire emerges from multiple disturbances to most shape microbial and nitrogen dynamics in a deciduous forest. (June 2022) - Martin, Gregory D.; Morrissey, Ember M.; Carson, Walter P.; Freedman, Zachary B.
Abstract: Healthy forests are vital components of terrestrial ecosystems for their raw materials, high biodiversity, cycling of nutrients, and potential to sequester carbon. However, these ecosystems are sensitive to disturbances, and anthropogenic activities pose a serious threat to forest ecosystems globally. For example, human activities have dramatically altered multiple historical disturbance regimes in forests, including suppressing fire, increasing the density of large herbivores, and reducing the size of canopy gaps, among other disturbances. Such disturbances can have dramatic impacts on microbially-mediated forest soil functions, but more research is needed to determine the collective impacts of these disturbances. In this study, we investigated the interactive effects of disturbances, namely the legacies of fire, large herbivore densities, and canopy gap creation, in a deciduous forest soil. We determined that forest floor and mineral soil carbon and nitrogen pools were shaped by multiple disturbances, but fire was more influential than the other disturbances. The abundance of several functionally-relevant microbial taxa were significantly impacted by fire, and the effect was more pronounced in the mineral soil than in the forest floor. Together, these findings demonstrate that multiple disturbances, especially a legacy of fire, exerts long-term control over soil carbon, nitrogen and microbial dynamics in a deciduous forest system. Graphical abstract: Image 1 Highlights: A legacy of fire led to less C in the forest floor and more NH4 + in mineral soil. Fire increased N-cycling prokaryotic guilds in the forest floor and mineral soil. Soil chemistry was strongly linked with N-cycling prokaryotic guild abundance.